Real-time Analytics with Storm and Cassandra - Saxena, Shilpi; Saxena, Shilpi (Packt Publishing, 2015)
This book will teach you how to use Storm for real-time data processing and to make your applications highly available with no downtime using Cassandra.The book starts off with the basics of Storm and its components along with setting up the environment for the execution of a Storm topology in local and distributed mode. Moving on, you will explore the Storm and Zookeeper configurations, understand the Storm UI, set up Storm clusters, and monitor Storm clusters using various tools. You will then add NoSQL persistence to Storm and set up a Cassandra cluster. You will do all this while being guided by the best practices for Storm and Cassandra applications. Next, you will learn about data partitioning and consistent hashing in Cassandra through examples and also see high availability features and replication in Cassandra. Finally, you'll learn about different methods that you can use to manage and maintain Cassandra and Storm.